Clubs and standards: The role of industry consortia in standardization of wireless telecommunications - Aija Leiponen (The Research Institute of the Finnish Economy (ETLA), 2005)
This empirical study explores firms' standard-setting strategies in wireless telecommunications. A quantitative case study of one standards development organization, the Third Generation Partnership Project (3GPP), provides measures for firms' ability to influence technical standardization outcomes. These measures are related to member firms' cooperative activities outside of the 3GPP. A particular focus is on firms' activities in other cooperative technical organizations such as industry associations and fora that aim at developing or promoting specific wireless technologies. Estimation results suggest that firms with dense connections to other 3GPP members outside of the standards development organization through the various cooperative organizations are more influential within the 3GPP. This supports the argument that leading technology firms' standard-setting strategies do not simply involve choosing the one optimal form of cooperation, but setting up a constellation of cooperative arrangements with their peers, to maximize opportunities to influence the industry. However, the majority of member firms in a standards development organization such as 3GPP do not participate in working groups with the goal of influencing standardization outcomes. Instead, these firms are probably trying to learn about new technologies and the potential evolution of markets from the leading companies. It is in their interest to make sure that coordinated outcomes are achieved in the industry. Overall, the results point to the significant role played by private and semi-public cooperative arrangements in determining standardization outcomes. However, these organizations are largely outside of public policy or oversight. In order to enable access to standardization and subsequently network markets for all kinds of firms, standards policy makers might consider supporting consortia activity of small firms and setting some rules about open access.
Keywords: 330; Standard setting; wireless telecommunication; cooperative arrangements; Normung; Funktechnik; Nachrichtentechnik; Unternehmenskooperation